Strategi Visual Merchandising Dengan Meningkatkan Tampilan Display Tenant Fashion Studi Kasus Pada Laswee Creative Space - Larasati, Asri (Wimba : Jurnal Komunikasi Visual, 2024)
One of the important entities supporting creativity in Bandung is Laswee Creative Space. However, there are issues in visual merchandising, particularly in the display of fashion tenants, which appears cluttered and unattractive. Poor display arrangements can diminish the appeal and image of Laswee as a creative hub. Visual merchandising plays a crucial role in creating a unique shopping experience. The use of elements such as lighting, color, and proper product arrangement can enhance the attractiveness and effectiveness of the display. This research aims to optimize visual merchandising strategies by improving the display of fashion tenants at Laswee Creative Space. The research employs a design thinking approach that involves five stages: empathize, define, ideate, prototype, and testing. Data collection was conducted through observation, interviews, questionnaires, and secondary data. The collected data was then analyzed using SWOT analysis. The findings reveal that the use of mannequins in the visual merchandising strategy at Laswee Creative Space significantly impacts the shopping experience of visitors and their perception of the area as a creative hub. By designing creative and attractive mannequin displays, Laswee Creative Space can create an inspiring and captivating environment for visitors. Keywords: Laswee Creative Space, Visual Merchandising, Design Thinking